2016
DOI: 10.1371/journal.pone.0162235
|View full text |Cite|
|
Sign up to set email alerts
|

Curiosity Search: Producing Generalists by Encouraging Individuals to Continually Explore and Acquire Skills throughout Their Lifetime

Abstract: Natural animals are renowned for their ability to acquire a diverse and general skill set over the course of their lifetime. However, research in artificial intelligence has yet to produce agents that acquire all or even most of the available skills in non-trivial environments. One candidate algorithm for encouraging the production of such individuals is Novelty Search, which pressures organisms to exhibit different behaviors from other individuals. However, we hypothesized that Novelty Search would produce su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 34 publications
0
40
0
Order By: Relevance
“…We recommend that other workers adopt psychometric approaches to assess general intelligence in animals, so that we can start to understand general intelligence in a broader comparative context. Finally, we urge those interested in the evolution of animal brains and intelligence to consider these phenomena in the light of recent discoveries in scientific computation germane to the evolution of both modular [169] and general intelligence [170]. Computer simulations of evolving organisms have revealed that modularity evolves in neural and other networks as a by-product of selection for minimizing connection costs among nodes [169].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recommend that other workers adopt psychometric approaches to assess general intelligence in animals, so that we can start to understand general intelligence in a broader comparative context. Finally, we urge those interested in the evolution of animal brains and intelligence to consider these phenomena in the light of recent discoveries in scientific computation germane to the evolution of both modular [169] and general intelligence [170]. Computer simulations of evolving organisms have revealed that modularity evolves in neural and other networks as a by-product of selection for minimizing connection costs among nodes [169].…”
Section: Discussionmentioning
confidence: 99%
“…Stanton & Clune [170] have recently developed a new evolutionary algorithm yielding digital organisms that acquire as many skills as possible during their lifetime. We hope that the ability to evolve …”
Section: Discussionmentioning
confidence: 99%
“…As a result, most current evolutionary algorithms produce domain-specific intelligence in machines that rarely possess more than a small set of skills, and they are thus suited to performing only tasks that demand that particular skill set. Although an intrinsic motivation to explore the environment has been imitated in artificial agents via machine learning (Schmidhuber 1991;Oudeyer et al 2007), the production of generalist learners within an evolutionary context remains highly problematic (Stanton & Clune 2016).…”
Section: The Evolution Of General Intelligence In All Animals and Macmentioning
confidence: 99%
“…Indeed, QD draws inspiration from the idea of rewarding divergence to find the necessary steps towards high performing areas of the search space. In divergent search, artificial evolution is not guided by a fitness tied to the ultimate objective of the problem, but instead rewards directly the diversity of solutions, based on notions such as novelty [8], surprise [9] or curiosity [10]. QD combines the divergent properties of divergent search with localized convergence, as will be discussed below.…”
Section: Quality Diversity Approachesmentioning
confidence: 99%